PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL PEMBELAJARAN PKn PADA SISWA KELAS VI SDN 3 SUKAJAWA BANDAR LAMPUNG TAHUN PELAJARAN 2018/2019 - Karlina Karlina (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
Efforts to improve student learning completeness require effective and efficient learning methods. By using the right learning model students are expected to master the expected competencies. Jigsaw is one part of the cooperative learning model. The Jigsaw type learning model requires student activeness in following learning. Students have many opportunities to express opinions and process the information obtained and can improve communication skills. The purpose of this study was to improve the Civics learning outcomes of the Inter-State Cooperation in Southeast Asia using the Jigsaw type learning model. The research subjects were Grade VI students of SDN 3 Sukajawa in the 2018/2019 academic year. The research used two rounds of Classroom Action Research. Each round consists of: planning, action and observation, reflection, and revision. Data collection techniques using observation and tests. Based on the results of the study, it can be concluded that there is an increase in the learning outcomes of the VI grade students of SDN 3 Sukajawa after the implementation of the Jigsaw cooperative learning model in Civics learning, this can be seen in the initial conditions of the acquisition of an average value of 52.5 with the highest score of 70. In cycle I acquisition of an average value of 60.69 with the highest score of 90. In the second cycle, the acquisition of an average value of 74.14 with the highest value of 100. Completeness of learning has increased, in the initial conditions of learning completeness by 48.28%, in the first cycle it has increased to 65.22% and in cycle II to 89.65%.